Neonatal encephalopathy due to birth asphyxia and trauma: global trends and disparities - Du, Fengling; Gu, Long; Wang, Junyi; Zhang, Chan; Li, Chun; Zhao, Shuai; Shen, Yunchuan; Luo, Mei; Yan, Yun; Zhou, Jian; Dong, Wenbin (Frontiers in Public Health, 2025)
BackgroundNeonatal encephalopathy due to birth asphyxia and trauma (NE-BAT) is a leading cause of neonatal mortality and long-term neurodevelopmental disabilities, particularly in low- and middle-income regions.MethodsUsing the Global Burden of Disease (GBD) 2021 dataset, we analyzed global incidence, prevalence, mortality, and disability-adjusted life years (DALYs) of NE-BAT from 1990 to 2021. We examined age-standardized rates, estimated annual percentage changes (EAPC), socio-demographic index (SDI) quintiles, gender differences, and used autoregressive integrated moving average (ARIMA) models for 2031 projections.ResultsFrom 1990 to 2021, global age-standardized incidence rate declined from 20.22 to 17.16 per 100,000 (EAPC: −0.56), while prevalence increased from 129.73 to 242.03 per 100,000 (EAPC: 2.16). Males had higher incidence (19.93 vs. 14.18 per 100,000) and prevalence (291.46 vs. 191.38 per 100,000) than females. Mortality declined from 13.81 to 9.75 per 100,000 (EAPC: −1.24), and DALYs decreased from 1270.67 to 932.14 per 100,000 (EAPC: −1.12). Low SDI locations had NE-BAT-specific mortality rates 27 times higher than high SDI locations (17.77 vs. 0.66 per 100,000 in 2021). Projections to 2031 suggest continued declines in incidence and DALYs but rising prevalence and mortality rates.ConclusionWhile global burden of NE-BAT has improved through reduced incidence and DALYs, persistent gender and regional disparities, along with rising prevalence rates, pose ongoing challenges. Targeted interventions addressing these disparities, particularly in low SDI locations, are essential to improve neonatal outcomes and reduce health inequalities.